Dual role of HupF in the biosynthesis of [NiFe] hydrogenase in Rhizobium leguminosarum - Albareda, Marta (BioMed Central, 2012)
BACKGROUND: [NiFe] hydrogenases are enzymes that catalyze the oxidation of hydrogen into protons and electrons, to use H(2) as energy source, or the production of hydrogen through proton reduction, as an escape valve for the excess of reduction equivalents in anaerobic metabolism. Biosynthesis of [NiFe] hydrogenases is a complex process that occurs in the cytoplasm, where a number of auxiliary proteins are required to synthesize and insert the metal cofactors into the enzyme structural units. The endosymbiotic bacterium Rhizobium leguminosarum requires the products of eighteen genes (hupSLCDEFGHIJKhypABFCDEX) to synthesize an active hydrogenase. hupF and hupK genes are found only in hydrogenase clusters from bacteria expressing hydrogenase in the presence of oxygen. RESULTS: HupF is a HypC paralogue with a similar predicted structure, except for the C-terminal domain present only in HupF. Deletion of hupF results in the inability to process the hydrogenase large subunit HupL, and also in reduced stability of this subunit when cells are exposed to high oxygen tensions. A ΔhupF mutant was fully complemented for hydrogenase activity by a C-terminal deletion derivative under symbiotic, ultra low-oxygen tensions, but only partial complementation was observed in free living cells under higher oxygen tensions (1% or 3%). Co-purification experiments using StrepTag-labelled HupF derivatives and mass spectrometry analysis indicate the existence of a major complex involving HupL and HupF, and a less abundant HupF-HupK complex. CONCLUSIONS: The results indicate that HupF has a dual role during hydrogenase biosynthesis: it is required for hydrogenase large subunit processing and it also acts as a chaperone to stabilize HupL when hydrogenase is synthesized in the presence of oxygen.